THE USE OF E-RESOURCES FOR YOUNG LEARNERS ENGLISH TEACHING MATERIALS - Meisani, Diah Royani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
As internet technology has become more influential and cultured, online or e-resources are nowadays present as alternatives for teaching materials. The resources themselves play an important role in lesson planning, instruction delivery, and take a part in determining the learning achievement. This study was conducted to investigate the forces that drive elementary school English teachers (N = 178) in utilizing online teaching materials together with the benefits and challenges they faced in using them. From the questionnaire, it was revealed that almost all respondents used and benefited from online resources taken from Google, YouTube, and other search engines. Further investigation through interviews revealed prevalent responses on e-learning materials utilization that are categorized as follows: accessibility, practicality, authenticity, and variety. Other benefits, such as the features of online resources that positively attract young learners in foreign language learning are meaningfully advantageous as they improve students’ learning engagement (SLE). These findings support evidence for e-learning resources as teaching materials for overcoming the shortage of teaching guidelines and materials in English for Young Learners (EYL) classes. Teachers’ responses towards the challenges in using this type of material lead to the implication that schools and other related stakeholders should take serious concerns to equip EYL teachers with professional development or in-service training, particularly in teaching material development and online resources integration.